The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Turkey. (4th May 2017) - Öztürk, Can
Abstract : As it is not a member of the European Union, Turkey has not yet adopted EU accounting directives by law. Instead, Turkish standard setting authority adopted International Financial Reporting Standards for entities that have public accountability and has recently prepared the draft Turkish financial reporting standard for non-publicly accountable entities that are subject to independent audit: Framework for Local Financial Reporting. This national standard is influenced by European accounting directive 2013/34, international financial reporting practices and UK experience in addition to national accounting rules.